PERSONAL SELLING TABLOID BISNIS SULAWESI DALAM MENARIK MINAT PEMASANG IKLAN (Jurnal Washiyah: Jurnal Kajian Dakwah dah Komunikasi, 2020)
This study aims to determine the personal selling conducted by the Bisnis Sulawesi Tabloid in attracting interest in advertising and to determine the factors supporting and inhibiting the personal selling of Bisnis Sulawesi Tabloid in attracting interest in advertising. The results showed that personal selling conducted by the Bisnis Sulawesi Tabloid in attracting interest in advertising is looking for prospects, setting goals, communicating, selling, and serving. The supporting factor is that Bisnis Sulawesi has a good rating. While the inhibiting factors are the extent of deployment, production machinery and company personnel cross-duty.